IDENTIFICATION AND ANALYSIS OF WEED VEGETATION AS Ganoderma PRESENCE MARKER ON OIL PALM PLANTATION - Wismaroh Sanniwati Saragih; Edison Purba; Koko Tampubolon (Jurnal Natural, 2018)
Weeds on oil palm plantations can also be the host of Basal Stem Rot caused by Ganoderma. This study aims to identify and analyze of weed vegetation using visual estimation and squares method as Ganoderma presence marker on oil palm plantations. This research was conducted in block 17, 16, and 6 of VII afdeling, Rambutan Estate in Serdang Bedagai Regency on December 2017 to March 2018. This research used survey method with visual estimation and squares. The data used is absolute density, relative density, absolute frequency, relative frequency, important value indeks, Summed Dominance Ratio (SDR) and dry weight. Data analysis using IBM SPSS Statistics 20 software. The results showed that different weed species between oil palm was infected and uninfected by Ganoderma with visual estimation method is Cyclosorus aridus (14.78%) where as with squares method are Cyperus rotundus (10.60%), and Stenochlaena palustris (7.76%) with temperature range 28.67 to 30.80oC and moisture amount 60.67 to 77.33%.